Erasmus and the Novum Instrumentum. - Holder, R. Ward (Church History & Religious Culture, 2016)
This issue of Church History and Religious Culture celebrates the five hundred years of influence to both religious life and piety and to scholarship that the publication of the Novum Instrumentum engendered. Truly, littera scripta manet. The essays gathered here challenge presently held notions of what Erasmus was doing in creating a critical Greek New Testament, his status as a theologian, his relationship to Jerome and the fashioning of a biblical eleoquence, his relationship to Martin Luther, and even the influence of Erasmus’s work itself. By challenging presently held notions, these essays pay tribute to the example that Erasmus set, and offer a fitting remembrance to the 500th anniversary of his Novum Instrumentum.